The spectroscopic foundation of radiative forcing of climate by carbon dioxide. Issue 10 (24th May 2016) - Mlynczak, Martin G.; Daniels, Taumi S.; Kratz, David P.; Feldman, Daniel R.; Collins, William D.; Mlawer, Eli J.; Alvarado, Matthew J.; Lawler, James E.; Anderson, L. W.; Fahey, David W.; Hunt, Linda A.; Mast, Jeffrey C.
Abstract: The radiative forcing (RF) of carbon dioxide (CO2 ) is the leading contribution to climate change from anthropogenic activities. Calculating CO2 RF requires detailed knowledge of spectral line parameters for thousands of infrared absorption lines. A reliable spectroscopic characterization of CO2 forcing is critical to scientific and policy assessments of present climate and climate change. Our results show that CO2 RF in a variety of atmospheres is remarkably insensitive to known uncertainties in the three main CO2 spectroscopic parameters: the line shapes, line strengths, and half widths. We specifically examine uncertainty in RF due to line mixing as this process is critical in determining line shapes in the far wings of CO2 absorption lines. RF computed with a Voigt line shape is also examined. Overall, the spectroscopic uncertainty in present‐day CO2 RF is less than 1%, indicating a robust foundation in our understanding of how rising CO2 warms the climate system. Key Points: Line mixing and line shape uncertainties contribute < 0.7% error to CO2 radiative forcing Line strength and half‐width uncertainties contribute < 0.3% error to CO2 radiative forcing Overall spectroscopic uncertainty in CO2 radiative forcing is < 1%